ICMS ecológico : uma proposta para a região do semi-árido de Sergipe - Santos, Carlos Anselmo Dias (2006)
Since the 60´s a group of searchers in front of same aspects as: geographic growing, food production, etc, looking for analyze the future situation of the man kind in related to Environment. In this aspect, in consequence of the environmental worry there is the Conference in Rio de Janeiro named Rio 92, with main subject the approval of 21st agenda, whose main objective is to stimulate the environmental conservation and preservation. In this context, the state of Paraná became the first in the creation and implementation of Ecological ICMS, an economic instrument that has as main functions: the compensatory function and stimulating function. This way, foundated in the Federal and State Constitution, in the study executed about the Sergipe´s ICMS and through the stimulating function, the present work has as objectives: the implementation and establishing of the Ecological ICMS in the semi-arid region in the Sergipe state. This way, we will search for identify groups of towns that present similitude and still establish tendency functions through the years in the resort available in the piece ICMS.